Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Certainly! Let's go through the steps for each part of the question.
### Part (a)
We are given the function [tex]\( f(x) = 7x - 6 \)[/tex].
To find [tex]\( f(4) \)[/tex]:
1. Substitute [tex]\( x = 4 \)[/tex] into the function:
[tex]\[ f(4) = 7(4) - 6 \][/tex]
2. Perform the multiplication:
[tex]\[ 7 \times 4 = 28 \][/tex]
3. Subtract 6 from 28:
[tex]\[ 28 - 6 = 22 \][/tex]
Therefore, the value of [tex]\( f(4) \)[/tex] is [tex]\( 22 \)[/tex].
### Part (b)
We now need to find the value of the inverse function [tex]\( f^{-1}(22) \)[/tex].
To find the inverse function, we start by expressing [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex] from the original function:
[tex]\[ y = 7x - 6 \][/tex]
Next, solve for [tex]\( x \)[/tex]:
1. Add 6 to both sides:
[tex]\[ y + 6 = 7x \][/tex]
2. Divide both sides by 7:
[tex]\[ x = \frac{y + 6}{7} \][/tex]
Thus, the inverse function is:
[tex]\[ f^{-1}(y) = \frac{y + 6}{7} \][/tex]
To find [tex]\( f^{-1}(22) \)[/tex]:
1. Substitute [tex]\( y = 22 \)[/tex] into the inverse function:
[tex]\[ f^{-1}(22) = \frac{22 + 6}{7} \][/tex]
2. Add 22 and 6:
[tex]\[ 22 + 6 = 28 \][/tex]
3. Divide 28 by 7:
[tex]\[ \frac{28}{7} = 4 \][/tex]
Therefore, the value of [tex]\( f^{-1}(22) \)[/tex] is [tex]\( 4 \)[/tex].
### Summary
- The value of [tex]\( f(4) \)[/tex] is [tex]\( 22 \)[/tex].
- The value of [tex]\( f^{-1}(22) \)[/tex] is [tex]\( 4 \)[/tex].
### Part (a)
We are given the function [tex]\( f(x) = 7x - 6 \)[/tex].
To find [tex]\( f(4) \)[/tex]:
1. Substitute [tex]\( x = 4 \)[/tex] into the function:
[tex]\[ f(4) = 7(4) - 6 \][/tex]
2. Perform the multiplication:
[tex]\[ 7 \times 4 = 28 \][/tex]
3. Subtract 6 from 28:
[tex]\[ 28 - 6 = 22 \][/tex]
Therefore, the value of [tex]\( f(4) \)[/tex] is [tex]\( 22 \)[/tex].
### Part (b)
We now need to find the value of the inverse function [tex]\( f^{-1}(22) \)[/tex].
To find the inverse function, we start by expressing [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex] from the original function:
[tex]\[ y = 7x - 6 \][/tex]
Next, solve for [tex]\( x \)[/tex]:
1. Add 6 to both sides:
[tex]\[ y + 6 = 7x \][/tex]
2. Divide both sides by 7:
[tex]\[ x = \frac{y + 6}{7} \][/tex]
Thus, the inverse function is:
[tex]\[ f^{-1}(y) = \frac{y + 6}{7} \][/tex]
To find [tex]\( f^{-1}(22) \)[/tex]:
1. Substitute [tex]\( y = 22 \)[/tex] into the inverse function:
[tex]\[ f^{-1}(22) = \frac{22 + 6}{7} \][/tex]
2. Add 22 and 6:
[tex]\[ 22 + 6 = 28 \][/tex]
3. Divide 28 by 7:
[tex]\[ \frac{28}{7} = 4 \][/tex]
Therefore, the value of [tex]\( f^{-1}(22) \)[/tex] is [tex]\( 4 \)[/tex].
### Summary
- The value of [tex]\( f(4) \)[/tex] is [tex]\( 22 \)[/tex].
- The value of [tex]\( f^{-1}(22) \)[/tex] is [tex]\( 4 \)[/tex].
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.